Do older people perceive cancer prevention and early detection to be worthwhile? Implications for prevention - Ngune, Irene; Howat, Peter; Maycock, Bruce; Slevin, Terry (The Australian Journal of Primary Health, La Trobe University, 2009)
Despite evidence that suggests modifying risk factors at any age can reduce the risk of cancer, many older people fail to take relevant preventive actions. The objectives of the project were to assess whether older people perceived taking actions to prevent cancers as worthwhile after the age of 60 years. Fifty men (19) and women (31) 60 years and older (mean age 68 years) participated in seven focus groups to assess their perceptions of preventive health actions and barriers and motivators in relation to cancer prevention. Most participants reported not adhering to preventive actions for cancer. Many did not perceive the benefits if the actions are initiated after the age of 60 years, and some risk factors were not perceived to be related to cancer. There was strong agreement that screening for cancer was worthwhile after the age of 60 years. It appears that awareness programs specifically tailored to seniors may be desirable to promote cancer prevention within a context of chronic disease prevention in general.